Estudo da influência das competências dos níveis operacionais sobre os processos de estratégia: o caso da empresa farmacêutica MERCK S.A - Gomes, Saulo de Oliveira (2005)
Based on the approaches and studies on the subject of organizational strategies aimed at intra-firm aspects, resources and competencies developed by organizations have been identified as the key elements toward assessing and explaining a company¿s performance. Considering such perspective, it has been observed that the development and effective implementation of organizational strategies depend on the skills and knowledge supplied by workers who are motivated or led to contribute with their effort so as to meet the organization¿s goals. Considering this, the purpose of this dissertation is to identify how the competencies of the operational levels of an organization are mobilized to contribute to the shaping and implementation of organizational strategies. This assessment was accomplished by observing the existing relationships between organizational and human resources management processes and processes of short term and long term strategies in a company of the pharmaceutical industry. The analysis of the evidence collected during the observation of this company has shown a strong link between personnel processes and the accomplishment of short term strategic goals, and a weaker link with the establishment of long term strategies. As a rule, the corporation¿s operational levels have little influence on the strategic planning and its implementation, even though the company uses a model of competencies designed to create more effective and measurable relationships between individual competencies and the company¿s performance.